Personal ultraviolet Radiation exposure in a cohort of Chinese mother and child pairs: the Chinese families and children study - Michael G. Kimlin; Liwen Fang; Yajing Feng; Linhong Wang; Ling Hao; Jing Fan; Ning Wang; Fanwen Meng; Ruilan Yang; Shu Cong; Xiaofeng Liang; Baohua Wang; et al. (BMC, 2019)
Abstract Background Few studies in China have examined personal ultraviolet radiation (UVR) exposure using polysulfone dosimetry. Methods In this study, 93 mother and adolescent child pairs (N = 186) from two locations in China, one rural (higher latitude) and one urban (lower latitude), completed 3 days of personal UVR dosimetry and a sun/clothing diary, as part of a larger pilot study. Results The average daily ambient UVR in each location as measured by dosimetry was 20.24 Minimal Erythemal Doses (MED) in the rural location and 20.53 MED in the urban location. Rural mothers had more average daily time outdoors than urban mothers (5.5 h, compared with 1.5 h, in urban mothers) and a much higher daily average personal UVR exposure (4.50 MED, compared with 0.78 MED in urban mothers). Amongst adolescents, rural males had the highest average daily personal UVR exposure, followed by rural females, urban females and urban males (average 2.16, 1.05, 0.81, and 0.48 MED, respectively). Conclusions Although based on small numbers, our findings show the importance of geographic location, age, work/school responsibilities, and sex of the adolescents in determining personal UVR exposure in China. These results suggest that latitude of residence may not be a good proxy for personal UVR exposure in all circumstances.